Fighting the wrong enemy : antiglobal activists and multinational enterprises - Graham, Edward M. (Institute for International Economics WashingtonUS, 2000)
Focuses on why the Multilateral Agreement of Investment (MAI) failed and the implication of that failure for global governance. Examines whether the organized opposition to increased economic integration, was the main reason for the failure. Concludes that it has not but, rather, that the MAI negotiations, were in deep trouble much earlier because of fundamental policy disagreements over foreign direct investment itself among some of the key OECD governments. Seeks to draw lessons from the MAI episode for international approaches to foreign direct investment and globalization more generally.